UPAYA MEMAHAMI RETORIKA POLITIK PRESIDEN OBAMA (SUATU TINJAUAN PRAGMATIK) - Fikri Fikri (Institut Agama Islam Negeri Palopo, 2014)
This study is to discuss briefly political rhetoric of President Obama as expressed in The Jakarta Postdaily newspaper. It attempts to explore the statements of his political rhetoric in the perspective of pragmatics study, particularly in the theory of implicature. The findings indicated that (1) Obama often used a metaphor when he delivered his speech; He also presented statements in group of three in his speech to strengthen his political message; He liked to use pronomina I and we for saving his political deeds. (2) to understand his political rhetoric of Obama, the audience (receptor) should be able to figure out the text, context, and pre-assumption between speaker and listener.